Review of Waterflooding Performance in Stratified Reservoirs. - El-Khatib, Noaman A.F. (2010)
Factors affecting oil recovery in waterflooding are reviewed. The recovery factor in waterflooding is the product of the displacement efficiency and the volumetric sweep efficiency. The different methods for the prediction of waterflooding Performance in Stratified Reservoirs are reviewed. The methods are grouped into two main categories depending on the degree of communication between the different layers. The method of Dykstra-Parsons for non-communicating reservoirs is outlined and its extensions are discussed. The models of Hiatt and Hearn for communicating reservoirs are reviewed and the concept of pseudo-relative permeability functions is presented. The application of these models for systems with log-normal permeability distributions by Warren and Cosgrove is outlined. The analytical closed form solution of El-Khatib and the developed generalized correlation charts are presented. The effect of gravity crossflow and non-newtonian fluids are presented. A model is developed for inclined stratified reservoirs. A dimensionless gravity number is found to characterize the effect of dip angle and density difference between the displacing and displaced fluid. The effects of the gravity number, mobility ratio and coefficient of permeability variation on the performance is investigated and discussed.